An Improved Power Factor Correction for Interleaved Flyback Switched Mode Power Supply - Sasikala, K; Krishna Kumar, R (International Journal of Engineering and Technology, 2018)
Nowadays the use of electronic equipment finds a progressive development in the modern world. Hence it becomes a mandate to check whether the harmonic content of line current of any electronic device which is connected to the ac supply meets the appropriate standards. This demand is satisfied by implementing the Power Factor Correction (PFC) circuit in order to make the input current to be in sinusoidal in nature and in-phase with the input voltage. Numerous solutions are available to make the line current almost sinusoidal. This paper deals with the inclusion of passive PFC in the interleaved Fly back SMPS to improve the power factor. The proposed work also examines the reduction of current ripple at the output using interleaved converter.Â Â